Aggression, Conflict and Peace ResearchMental health problems, family functioning and social support among children survivors of Colombia’s armed conflict (2020)
Purpose - Colombia presents with one of the largest armed conflicts in the world. Children exposed directly or indirectly to armed conflicts live the emotional footprints left by war. This study identified mental health problems among children survivors of Colombia’s armed conflict and associated factors. Design/methodology/approach – A cross-sectional study with (n=80) children aged 7 to 11 years (M=9.8 years; SD= 1.4) was conducted using the Child Behavior Checklist, Family APGAR, and MOS social support survey adaptation to children. Linear regression analyses were also performed with emotional and behavioral problems as the outcomes and related factors as the predictors. Findings - Clinical levels of emotional and behavioral problems were found in 56.3% of children. Internalizing problems (63.7%) were more common than externalizing problems (51.2%). Older children had greater emotional problems at the trend level, and those with higher functioning families had lower emotional problems. Children with higher perceived social support had lower behavior problems at the trend level. Research limitations/implications - This study includes a sample facing multiple risks and uses a holistic approach to consider family and social resources that may support children who are survivors of the armed conflict in Colombia. These results provide a foundation for future promotion and prevention programs related to children’s mental health problems to support peacebuilding within the framework of the Colombian post-conflict process. Originality/value – To the best of authors’ knowledge, this is the first study to collect empirical data on the mental health of children survivors of Colombia’s armed conflict focused in the Atlantic Department.